Role of Cortisol and Testosterone in Risky Decision-Making: Deciphering Male Decision-Making in the Iowa Gambling Task - Singh, Varsha (Frontiers in Neuroscience, 2021)
Despite the widely observed high risk-taking behaviors in males, studies using the Iowa Gambling Task (IGT) have suggested that males choose safe long-term rewards over risky short-term rewards. The role of sex and stress hormones in male decision-making is examined in the initial uncertainty and the latter risk phase of the IGT. The task was tested at peak hormone activity, with breath counting to enhance cortisol-regulation and cognitive processing. Results from IGT decision-making before and after counting with saliva samples from two all-male groups (breath vs. number counting) indicated that cortisol decline was independent of counting, IGT decision-making showed phase-specific alteration; decision making in the uncertainty phase was altered and that in the risk phase was stable. Working memory showed alteration, whereas inhibition task performance remained stable, potentially aligning with IGT’s phase-specific demands of working memory and inhibition. Results from hierarchical regressions for uncertainty and risk trials indicated that testosterone improved the model fit; cortisol was detrimental for decision making in uncertainty, whereas testosterone facilitated decision making in the risk trials. Cortisol-regulation accentuated hormones’ phase-specific effects on decision making. Aligned with the dual-hormone hypothesis, sex and stress hormones might jointly regulate male long term decision-making.